Far-right Radicalism in Ukraine in Past and Present - N. V. Rabotyazhev (Проблемы постсоветского пространства, 2021)
The article explores the ideological origins of Ukrainian radical nationalism, the formation and evolution of far-right political forces in post-Communist Ukraine, and the ideology of contemporary radical right-wing Ukrainian parties. Ukrainian far-right nationalism originated in the 1920s-30s. Its political embodiment was the Organization of Ukrainian Nationalists (OUN) which operated in Eastern Poland. Ideological foundation of the OUN was the concept of integral nationalism elaborated by Dmytro Dontsov. The OUN proclaimed the creation of Ukrainian sovereign state as its most important goal. The characteristic features of the ideology of Ukrainian radical far-right nationalism of that era were the priority of the interests of the Ukrainian nation, Russophobia, anti-communism, anti-liberalism, and the cult of power. Modern Ukrainian radical nationalists have adopted many of these concepts. In the 1990s, a number of extreme right-wing organizations emerged in Ukraine that declared themselves heirs of the traditions of Ukrainian nationalists of the first half of the XXth century. Some of the newly created parties tend towards integral nationalism, while others tend towards social nationalism, which combines ethnic nationalism with the idea of social justice. At the same time, all Ukrainian radical nationalists are characterized by an ethnic interpretation of the nation, a desire to create a mono-ethnic Ukrainian state, a negative attitude towards Russia and Russians, anti-communism, and commitment to the “third way” in economy. Critical of European liberal values, the Ukrainian far-right radicals are nonetheless in favor of Ukraine joining the EU and NATO, hoping that Ukraine’s Euro-Atlantic integration will distance it from Russia. Ukrainian radical nationalists actively participated in Euromaidan 2013-2014 and the overthrow of Victor Yanukovych’s regime. However, they have never (with the exception of the 2012 parliamentary elections) achieved any significant success in the elections to the Verkhovna Rada. Only a part of the population of Galicia votes for them. At the same time, some ideas previously put forward by the Ukrainian far right have in recent years to a certain extent entered the ideological baggage of respectable pro-European right-wing parties in Ukraine. Thus, the ideological and political influence of the Ukrainian far-right nationalists is more significant than it would be possible to assume based only on their electoral support.